Perlindungan Hukum Dokter dalam Kasus Self-Medication berdasarkan Undang-Undang Kesehatan - Esti, Wulan Rohmah Dwi Putri; Linda, Maura; Jaeni, Ahmad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Self-medication by patients without medical supervision can pose risks of complications, especially when involving the use of multiple medications simultaneously. Law No. 17 of 2023 on Health regulates the responsibilities of doctors but does not provide clear legal protection for doctors in handling complications arising from self-medication. This study analyzes the legal risks faced by doctors in such situations and identifies regulatory gaps that increase doctors' vulnerability to legal claims. The study recommends additional regulations to strengthen legal protection for doctors, as well as enhanced public education on the risks of self-medication, to ensure safe and responsible medical practices.